Program Bundling Produk Swb2p Dalam Perspektif Ekonomi Syariah ( Studi Kasus BMT UGT Nusantara Capem Muncar) - Fatimah, Siti; Khusnudin, Imam (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This article discusses the implementation of the Wadiah Term Savings (SWB2P) product bundling program at BMT UGT Nusantara Capem Muncar from a sharia economic perspective. The aim of this research is to analyze the effectiveness of the bundling program in increasing added value for customers and its impact on customer satisfaction and loyalty. The method used is a case study with data collection through interviews and document analysis. The research results show that the SWB2P bundling program provides significant benefits, such as lower administration costs and better accessibility to Islamic financial products. Apart from that, this program also increases customer satisfaction which leads to higher loyalty towards BMT UGT Nusantara. This research concludes that the SWB2P product bundling program can be an effective strategy in supporting sharia economic development and providing solutions to people's financial needs.